Uma análise da dinâmica do mercado de trabalho do Rio Grande do Sul nas recessões do Século XXI - Noschang, Cristian André (Universidade do Vale do Rio dos Sinos, 2022)
The recent Brazilian recessive economic cycles analyzed, starting in 2008 and the second in 2014 and ending in the fourth quarter of 2016, according to the Economic Cycles Dating Committee (Codace), have been identified as one of the worst in the country's history, both in terms of point of view of its duration as well as the magnitude of its effects. Structural indicators of the labor market reveal a record growth in the unemployment rate, in addition to the increase in informality, where there is usually a predominance of more precarious jobs compared to those existing in the regulated market. In this context, this dissertation investigates the impacts resulting from the economic crisis on the determinants of wage pressure, turnover and wage differences, using data from CAGEDE and RAIS in the period from 2007 to 2019, where it is observed that the mesoregion most affected by pressure salary and turnover is in the northwest of Rio Grande do Sul, this impact on the mesoregion is observed in the analysis by region. Through the Bry-Boschan algorithm, the recessions of this period are identified and, using the Oaxaca-Blinder method, an attempt is made to analyze the magnitude of this wage differential, which showed that the first recessions presented a higher average level of salary to those who maintained the employment, in the last recession there was a reduction in the average salary, where the unexplained component reflects this reduction pressured by the education variable.
Keywords: Recessão; Pressão salarial; Rotatividade; Mercado de trabalho Rio Grande do Sul; Bry-Boschan; Oaxaca-Blinder; Recession; Wage pressure; Turnover; Labor market Rio Grande do Sul; ACCNPQ::Ciências Sociais Aplicadas::Economia